2006
DOI: 10.1152/ajpregu.00069.2006
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in physical activity are closely associated with changes in body weight in adult female rhesus monkeys (Macaca mulatta)

Abstract: eron. Individual differences in physical activity are closely associated with changes in body weight in adult female rhesus monkeys (Macaca mulatta). Am J Physiol Regul Integr Comp Physiol 291: R633-R642, 2006. First published April 13, 2006; doi:10.1152/ajpregu.00069.2006.-The increased prevalence of overweight adults has serious health consequences. Epidemiological studies suggest an association between low activity and being overweight; however, few studies have objectively measured activity during a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 111 publications
8
49
1
Order By: Relevance
“…Although T-treated monkeys did not eat more calories than control animals, there was a strong trend toward the T-treated animals being less active than controls during the last 10 mo of this study. Studies in humans and animals found that individuals that are less active tend to gain more weight (17,47,82), which is consistent with the current data. Because activity levels were not assessed in our prior study (59) before T implants were placed, it is unknown if the T-treated animals had lower levels of activity at baseline or whether the decreased activity levels occurred later as a result of chronic T treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although T-treated monkeys did not eat more calories than control animals, there was a strong trend toward the T-treated animals being less active than controls during the last 10 mo of this study. Studies in humans and animals found that individuals that are less active tend to gain more weight (17,47,82), which is consistent with the current data. Because activity levels were not assessed in our prior study (59) before T implants were placed, it is unknown if the T-treated animals had lower levels of activity at baseline or whether the decreased activity levels occurred later as a result of chronic T treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The animals were fed ad libitum, and each meal was supplemented with a high-sugar, highcalorie treat (e.g., a cookie, snack cake, etc.). Previous studies have shown that monkeys eating this diet gained over 10% of their body weight within the first 5-6 mo of being on this diet (80,82).…”
Section: Western Style Dietmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, the fattest, least active monkeys showed the largest activity increases and weight losses. They also previously reported that spontaneous activity levels, but not food intake levels, were inversely correlated with weight gain over a 3-mo period in intact female rhesus macaques (706). These data, together with Lovejoy et al's (443) report that spontaneous activity decreases across the menopausal transition, identify physical activity and eating as important targets for future menopause research.…”
Section: R1226 Sex Differences In the Physiology Of Eatingsupporting
confidence: 52%
“…The characterization and selective breeding of these two groups of rats has lead to the identification of differences in food intake, feed efficiency, and the expression level of hypothalamic food intake regulatory peptides . Nonhuman primate studies indicate that there are large differences between individuals in high-fat-diet-induced weight gain and that the individuals with the highest levels of physical activity are the least likely to gain weight (Sullivan et al 2005;Sullivan et al 2006). Many investigators are currently using animal models to identify physiological, genetic, and neural circuit influences on susceptibility to diet-induced obesity.…”
Section: Animal Models Of Obesitymentioning
confidence: 99%